Human prominin-1 (CD133) is detected in both neoplastic and non-neoplastic salivary gland diseases and released into saliva in a ubiquitinated form. - Jana Karbanová; Jan Laco; Anne-Marie Marzesco; Peggy Janich; Magda Voborníková; Jaroslav Mokrý; Christine A Fargeas; Wieland B Huttner; Denis Corbeil (PLoS ONE)
Prominin-1 (CD133) is physiologically expressed at the apical membranes of secretory (serous and mucous) and duct cells of major salivary glands. We investigated its expression in various human salivary gland lesions using two distinct anti-prominin-1 monoclonal antibodies (80B258 and AC133) applied on paraffin-embedded sections and characterized its occurrence in saliva. The 80B258 epitope was extensively expressed in adenoid cystic carcinoma, in lesser extent in acinic cell carcinoma and pleomorphic adenoma, and rarely in mucoepidermoid carcinoma. The 80B258 immunoreactivity was predominately detected at the apical membrane of tumor cells showing acinar or intercalated duct cell differentiation, which lined duct- or cyst-like structures, and in luminal secretions. It was observed on the whole cell membrane in non-luminal structures present in the vicinity of thin-walled blood vessels and hemorrhagic areas in adenoid cystic carcinoma. Of note, AC133 labeled only a subset of 80B258-positive structures. In peritumoral salivary gland tissues as well as in obstructive sialadenitis, an up-regulation of prominin-1 (both 80B258 and AC133 immunoreactivities) was observed in intercalated duct cells. In most tissues, prominin-1 was partially co-expressed with two cancer markers: carcinoembryonic antigen (CEA) and mucin-1 (MUC1). Differential centrifugation of saliva followed by immunoblotting indicated that all three markers were released in association with small membrane vesicles. Immuno-isolated prominin-1-positive vesicles contained CEA and MUC1, but also exosome-related proteins CD63, flotillin-1, flotillin-2 and the adaptor protein syntenin-1. The latter protein was shown to interact with prominin-1 as demonstrated by its co-immunoisolation. A fraction of saliva-associated prominin-1 appeared to be ubiquitinated. Collectively, our findings bring new insights into the biochemistry and trafficking of prominin-1 as well as its immunohistochemical profile in certain types of salivary gland tumors and inflammatory diseases.